2016
DOI: 10.1007/s12529-016-9599-y
|View full text |Cite
|
Sign up to set email alerts
|

Illness Perceptions and Outcomes in Patients with Inflammatory Bowel Disease: Is Coping a Mediator?

Abstract: Purpose: Patients with inflammatory bowel disease (IBD) often experience severe impairment in different life domains. Psychological factors, such as illness perceptions and coping, may play a role in the adjustment to IBD as indicated by mental and physical health, activity and work impairment. The present study aimed at examining the assumption of the Common Sense Model (CSM) that coping mediates the relationship between illness perceptions and adjustment in patients with IBD. Method:In a cross-sectional desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
(73 reference statements)
2
26
0
Order By: Relevance
“…The assumption that pain influences coping behavior is not unexpected and has been previously put forward [ 22 , 23 ]. In accordance with the theory of the CSM, we observed that coping strategies of patients with FD affected their QoL, which is in keeping with observations in patients with other chronic disorders [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…The assumption that pain influences coping behavior is not unexpected and has been previously put forward [ 22 , 23 ]. In accordance with the theory of the CSM, we observed that coping strategies of patients with FD affected their QoL, which is in keeping with observations in patients with other chronic disorders [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…Despite American and European guidelines,32–34 only 12% of adult IBD services,35 compared with 67% of paediatric centres,36 provide access to a specialist psychologist. Failing to employ a preventative, rather than reactive, approach to psychological well-being in adult IBD populations37 is likely to impact negatively on health risk behaviours and self-management behaviours, with subsequent costs including from work impairment 38. Young people transitioning to adult care are also an at-risk group and may require further psychological assessment and screening of psychological morbidity with the known increased prevalence of depression through puberty 16.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in the available treatment options, IBD continues to have a negative impact on the quality of life of patients [35]. Many studies have focused on the impact of IBD on quality of life [36, 37], the need for information [38], strategies to adapt [39] and shared decision making [40]. Despite the funding and resources invested in the diagnosis and monitoring of IBD, few studies have focused on these activities.…”
Section: Introductionmentioning
confidence: 99%